Ridskolehästens välfärd : en jämförelsestudie om inhysningssystem kopplat till hästens benhälsa och skador - Iversby, Martine; Söderby, Moa (SLU/Dept. of Animal Environment and Health (until 231231), 2020)
The riding school horse is the most important asset for a riding school. Every individual is as important and if one of them gets injured it affects both the economy and the other healthy horses who then will have to work harder. Today, the way we usually keep our horses at the riding schools is not as different from the old military days. The most common housing system is that horses stay inside in boxes during nighttime and only go outside a few hours a day with other horses. There is research that can prove that the horses get their natural behaviors fulfilled when they are in groups and can move and eat as much as they want to. It is hard to find research about how housing affects the welfare of the riding school horses when it comes to leg health and if there is a link between housing system and injuries. The aim of the study was to compare the housing system at two different riding schools to see if there was any difference when it came to injured riding school horses. One of the riding schools had stables with boxes (BOX) and the other riding school used a group housing system (LOS). The questions examined in the study were: Does housing have any significance for the injuries causing lameness on a riding school horse? Does housing have any impact on how much a riding school horse stumbles during lessons? Can the housing system have an impact on the swelling of the horses’ legs? We used three different methods to measure the welfare of the riding school horses; compiling injury data from 2019, observations of riding lessons and compiling injury data from 2019 and measuring the circumference of the legs in the morning and the evening. There was a difference between the results of the housing systems for the horses that were injured and lame and could not participate in the daily activities. The mean value of horses in LOS was 10.6 days of injury per lameness, compared to 43.5 days for the horses in BOX. The horses that were kept in the stable had more swelling in their legs in the morning compared to the horses in the loose housing, where there was no difference between morning and evening. There was no difference with the amount of stumbling between the riding schools. The conclusions according to this study were that housing system had an influence on the swelling in the leg of the horses and that the housing system could have an effect on the injuries and the lameness on the riding school horses but more studies are needed to confirm this. The housing system did not seem to be the reason why the horses stumble during the riding lessons though, because it is usually the rider who affects the horses’ movements.